Exercise perspective on common cardiac medications - Dizon, Louise Anne (Integr Med Res, 2013)
Medicinal tablets have been used for a long time to treat cardiovascular disease. However, mortality rate is steadily increasing partly because of the patients’ sedentary lifestyle and unhealthy diet. By contrast, exercise has been systematically shown to have multiple benefits. Regular exercise training can prevent various diseases in healthy individuals. Combined exercise and cardiac medications may lead to the improvement of heart disease. Numerous exercise training pathways still need further investigations. How exercise can prevent, treat, or attenuate diseases remains somewhat elusive. Thus, this review will discuss cardiac medications in parallel with the mechanism of action of exercise.